PENERAPAN MANAJEMEN PERUBAHAN PADA ETOS KERJA ISLAMI TERHADAP PENGURANGAN RESIKO TERHADAP KINERJA KARYAWAN: STUDI LITERATUR - Adelika Adelika; Chuzaimah Batubara (CV. ADIBA AISHA AMIRA, 2023)
Identification of potential protective variables that can assist in the development of resilience will be made possible by better knowledge of the potential elements that prevent decreased life satisfaction and harmful side effects. Protective variables that can assist the development of resilience will be made possible by better knowledge of the elements that prevent decreased life satisfaction and harmful side effects. In particular, qualitative research methodologies are used. the attempt of this study to evaluate while descriptively, is descriptive in nature. In qualitative research, the emphasis is on process and meaning. The emphasis is on process and meaning. The theoretical basis serves as a guide so that the topic of study is in accordance with the actual situation. Several survey participants reported being able to go to religious services to relieve stress and to be able to go to places of worship to relieve stress. teachings encourage Islam Muslims to practice worship, especially prayer, as servants who seek Allah's help for help in prayer when they are experiencing problems in their lives. prayer when they experience problems in their life encourages Muslims to maintain their religious practices, religious practices including including prayer ,prayer,. A man may take the opportunity to protect all his hidden and repressed feelings until they are lifted from him; Based on the written opinion, it can be concluded that the description of Islamic work ethics, change and change management can take the power of a company or company, especially because the Islamic principles that are highly upheld bring many benefits and blessings. , which came later, would make the company even more advanced. Changes in the spirit of continuous improvement can improve the performance and expertise of each member of the school which can improve community teaching standards, which can improve teaching standards